Stock market reaction to inflation announcement in the Indian stock market: A sectoral analysis - Gurmeet Singh; Lakshmi Padmakumari (Cogent Economics & Finance, 2020)
This study investigates the reaction of stock returns to the inflation announcement using time series data from 2012 to 2018. To check the market efficiency or semi-strong efficiency of the Indian Stock Market for inflation announcement, we have used an event study methodology. We selected nine events based on consensus estimate and actual inflation number; we put events into subgroups based on over-estimation, under-estimation, and accurate estimation. We performed an event study on inflation-sensitive sectors such as Banking, Energy, Realty, Service, and FMCG. To check for the above objectives, we calculated Average Abnormal Return (AAR), Cumulative Abnormal Return (CAR), and Cumulative Average Abnormal Return (CAAR). The finding of the study suggests that there are considerable abnormal returns, which are a function of the sector and the regime. Some sectors are more sensitive to inflation announcements, and some regimes are again more sensitive to inflation announcements.
Keywords: E31; G41; 330; inflation; event studies; market efficiency